Longitudinal 16S rRNA data derived from limb regenerative tissue samples of axolotl Ambystoma mexicanum - Demircan, Turan (Sci Data, 2019)
The Mexican axolotl (Ambystoma mexicanum) is a critically endangered species and a fruitful amphibian model for regenerative biology. Despite growing body of research on the cellular and molecular biology of axolotl limb regeneration, microbiological aspects of this process remain poorly understood. Here, we describe bacterial 16S rRNA amplicon dataset derived from axolotl limb tissue samples in the course of limb regeneration. The raw data was obtained by sequencing V3–V4 region of 16S rRNA gene and comprised 14,569,756 paired-end raw reads generated from 21 samples. Initial data analysis using DADA2 pipeline resulted in amplicon sequence variant (ASV) table containing a total of ca. 5.9 million chimera-removed, high-quality reads and a median of 296,971 reads per sample. The data constitute a useful resource for the research on the microbiological aspects of axolotl limb regeneration and will also broadly facilitate comparative studies in the developmental and conservation biology of this critically endangered species.